A palaeontological perspective on the proposal to reintroduce Tasmanian devils to mainland Australia to suppress invasive predators. (April 2019) - Westaway, Michael C.; Price, Gilbert; Miscamble, Tony; McDonald, Jane; Cramb, Jonathon; Ringma, Jeremy; Grün, Rainer; Jones, Darryl; Collard, Mark
Abstract: The diversity of Australia's mammalian fauna has decreased markedly since European colonisation. Species in the small-to-medium body size range have been particularly badly affected. Feral cats and foxes have played a central role in this decline and consequently strategies for reducing their numbers are being evaluated. One such strategy is the reintroduction to the mainland of the Tasmanian devil, Sarcophilus harrisii . Here, we provide a palaeontological perspective on this proposal. We begin by collating published records of devil remains in Quaternary deposits. These data show that the range of devils once spanned all the main ecological zones in Australia. This indicates that they are capable of coping with a wide range of climatic and environmental conditions, and suggests that they could conceivably be reintroduced much more widely than has been thought possible hitherto. Subsequently, we examine fossils and coprolites from two sites in the Willandra Lakes Region World Heritage Area. These specimens not only support the suggestion that devils have wide ecological tolerances, but also suggest that devils can coexist with native small-to-medium species over long periods of time, which addresses one of the major concerns about the proposed reintroduction. We believe these two sets of palaeontological observations add substantial weight to the idea of reintroducing devils to the mainland as a way of suppressing cat and fox numbers.